Measuring KS0K± interactions using pp collisions at √s=7 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Köhler, Markus Konrad; Leardini, Lucia; et al. (Physics letters, 2019)
We present the first measurements of femtoscopic correlations between the KS0 and K± particles in pp collisions at s=7 TeV measured by the ALICE experiment. The observed femtoscopic correlations are consistent with final-state interactions proceeding solely via the a0(980) resonance. The extracted kaon source radius and correlation strength parameters for KS0K− are found to be equal within the experimental uncertainties to those for KS0K+. Results of the present study are compared with those from identical-kaon femtoscopic studies also performed with pp collisions at s=7 TeV by ALICE and with a KS0K± measurement in Pb-Pb collisions at sNN=2.76 TeV. Combined with the Pb-Pb results, our pp analysis is found to be compatible with the interpretation of the a0(980) having a tetraquark structure instead of that of a diquark.
Im Text sind "0" und "S" untereinander gestellt: die Zahl "0" hochgestellt, der Buchstabe "S" tiefgestellt
Im Text ist "plus-minus" hochgestellt
Available online 18 December 2018
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, V.J.G. Feuillard, P. Glässel, J. Kim, M. Kim, S. Klewin, M.K. Köhler, L. Leardini, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband [und weitere]
Gesehen am 25.06.2019